Shell morphology and reproductive anatomy of Levantina mardinensis (Gastropoda, Helicidae) from a new locality of Mardin, Turkiye - Ekin, Ihsan (Taylor & Francis Ltd, 2024)
The genus Levantina Kobelt, 1871, comprises 25 taxa inhabiting rocky environments across the Middle East. This study focuses on documenting a new location of L. mardinensis Kobelt, 1900, and provides a detailed analysis of its shell morphology and reproductive anatomy, contributing to the knowledge and conservation of this land snail from Mardin, southeastern Turkiye. The distribution of L. mardinensis is widespread in Mardin Province and extends into northern Syria and Iraq. The study provides measurements for previously unreported shell characteristics of specimens from Eskikale (Mardin), including aperture height, aperture width, spire height, and body whorl height, with high-resolution images for visual reference.
Keywords: Stylommatophora; shell measurement; reproductive anatomy